FAKTOR PEMBEDA DALAM KOMUNIKASI LINTAS BUDAYA ANTARA WISATAWAN ASING DENGAN MASYARAKAT LOKAL DI DESA WISATA KANDRI GUNUNGPATI KOTA SEMARANG - Nurul Khotimah (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2019)
Cultural diversity is a necessity in the human community in the world. Cultures have different value systems, so they determine different life goals, and determine ways of communicating that are strongly influenced by language, rules and norms in each culture. So that every communication activity with other people always contains the potential for cross-cultural or intercultural communication, because it will always be in a